THE INFLUENCE OF SHAYKH AHMAD MUSTAFA AL-MARAGHI’S THOUGHTS IN QURANIC EXEGESIS IN MALAYSIA - Yahaya, Amiratul Munirah; Abdullah, Mustaffa (Online Journal of Research in Islamic Studies, 2015)
This article discusses on the influence of Shaykh Ahmad Mustafa al-Maraghi’s thoughts (1883-1952) in the Quranic exegesis in Malaysia (before l963 known as Malaya) through his writing, Tafsir al-Maraghi. In the mid-20th century, the Kaum Muda (a modern reformist young fraction) had introduced modern reforms in Quranic exegesis. The modern reformists of Kaum Muda implanted the thoughts of al-Maraghi through modern religious schools known as madrasahs. Tafsir al-Maraghi influenced by Muhammad Abduh’s and Muhammad Rashid Rida’s approach of Tafsir al-Manar, was disseminated by the Malay graduates from Egypt which then made it as the main text and reference of the Quranic exegesis at madrasah and Arabic schools in Malaya. Thus, the al-Maraghi reforms expounded by the Kaum Muda scholars had improved the teaching and learning quality of Quranic studies in Malaya.